THE FINANCIAL SECTOR IN THE FINANCIAL SYSTEM ECONOMY: THEORETICAL ASPECTS - Yu. Kovalenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2015)
Broad and narrow approaches of the financial system are obtained. The difference between the financial system and the financial sector (the fi-nancial corporations sector) is shown. Organizational and institutional matrix of the financial system of the economy is proposed. Key positions of institutional sectors classification of Ukraine’s economy are analyzed, as well as the System of National Accounts with respect to the financial sec-tor of corporations. The structure of the sector of financial corporations in Ukraine is defined.